Building, testing and validating a set of home-made von Frey filaments: a precise, accurate and cost effective alternative for nociception assessment - de Sousa, Marcelo Victor Pires (2014)
BACKGROUND: A von Frey filament (vFF) is a type of aesthesiometer usually made of nylon perpendicularly held in a base. It can be used in paw withdrawal pain threshold assessment, one of the most popular tests for pain evaluation using animal models. For this test, a set of filaments, each able to exert a different force, is applied to the animal paw, from the weakest to the strongest, until the paw is withdrawn. NEW METHOD: We made 20 low cost vFF using nylon filaments of different lengths and constant diameter glued perpendicularly to the ends of popsicle sticks. They were calibrated using a laboratory balance scale. Building and calibrating took around four hours and confirmed the theoretical prediction that the force exerted is inversely proportional to the length and directly proportional to the width of the filament. RESULTS: The calibration showed that they were precise and accurate. We analyzed the paw withdrawal threshold assessed with the set of home-made vFF and with a high quality commercial set of 5 monofilaments vFF (Stoelting, Wood Dale, USA) in two groups (n=5) of healthy mice. COMPARISON WITH EXISTING METHODS: The home-made vFF precisely and accurately measured the hind paw withdrawal threshold (20.3±0.9 g). The commercial vFF have different diameters while our set has the same diameter avoiding the problem of lower sensitivity to larger diameter filaments. CONCLUSION: Building a set of vFF is easy, cost effective and, depending on the kind of tests, can increase precision and accuracy of animal nociception evaluation.